1.) Uporządkuj jednomiany : " * " -bd. znaczyć razy.
a) 3x * (-x) * 5yz * x * z * (-2)
b) abcbcacab

2.)Zredukuj wyrazy podobne. :
a) 2x + 3y - 4z + 5 - 3z + 6 + 4y + 5x - 1
b) 4a = 2b - 5 + 3c + 3a - 8b +2c - 4

3.) Oblicz wartości wyrażenia 3a - 8b + 2c - 4 ,
dla : a = 3,5 b= -4,1 c= 0,12

2

Odpowiedzi

  • Użytkownik Zadane
2010-02-11T18:09:29+01:00
1.) Uporządkuj jednomiany : " * " -bd. znaczyć razy.
a) 3x * (-x) * 5yz * x * z * (-2)=-3x³*5yz²*-2=30x³yz²
b) abcbcacab=a³b³c³

2.)Zredukuj wyrazy podobne. :
a) 2x + 3y - 4z + 5 - 3z + 6 + 4y + 5x - 1=7x+7y-7z+10
b) 4a - 2b - 5 + 3c + 3a - 8b +2c - 4=7a-10b+5c-9

3.) Oblicz wartości wyrażenia 3a - 8b + 2c - 4 ,
dla : a = 3,5 b= -4,1 c= 0,12
3*3,5+8*4,1+2*0,12-4=10,5+32,8+0,24-4=29,04
4 3 4
2010-02-11T18:14:55+01:00
2.
a) 2x + 3y - 4z + 5 - 3z + 6 + 4y + 5x - 1 = 7x + 7y - 7z +11
b) 4a + 2b - 5 + 3c + 3a - 8b + 2c - 4 = 7a - 6b + 5c - 9
3.
3a - 8b + 2c - 4, dla a = 3,5 b = -4,1 c = 0,12
3*3,5 - 8*(-4,1) + 2*0,12 - 4 = 10,5 + 32,8 + 0,24 - 4 = 43,54
1.
a) 3x * (-x) * 5yz * x * z * (-2) = -3x⁴ * 5yz² * (-2) = 30x⁴yz²
b) abcbcacab=a³b³c³
1 4 1